Soil Water Dynamics and Nitrate Leaching Under Corn–Soybean Rotation, Continuous Corn, and Kura Clover - Ochsner, T.E. (2020)
This study examines differences in soil water dynamics and nitrate‐nitrogen (N) leaching among cropping systems and N fertilizer sources in a long‐term experiment in southeastern Minnesota. Drainage and leachate concentrations were measured for 4 yr using automated equilibrium tension lysimeters installed below the root zone in replicated, large plots on a well‐drained silt loam soil. Soil water storage was monitored using water content reflectometers. Corn–soybean and continuous corn cropping systems exhibited similar soil water dynamics, drainage rates (145–202 mm yr−1), leachate nitrate N concentrations (21.3–25.6 mg L−1), and nitrate N leaching loads (30–75 kg ha−1 yr−1). Nitrate‐N concentrations in the leachate were similar whether N was added as urea (21.2 mg L−1) or anhydrous ammonia (25.7 mg L−1). A perennial kura clover (Trifolium ambiguum M. Bieb)‐based cropping system with no N fertilizer significantly altered soil water dynamics and resulted in lower (p < 0.10) drainage rates (53 mm yr−1), nitrate N concentrations (7.1 mg L−1), and nitrate N leaching loads (2–5 kg ha−1 yr−1) compared with corn–soybean or continuous corn, but also reduced corn grain yields. These impacts are generally consistent with a growing body of literature showing substantial environmental benefits of a kura clover living mulch system for corn production, but the economic viability of such a system is not yet proven.